(untitled) (Research, Society and Development, 2022)
Considering the relationships established between Information Science and the field of Health, as well as considering that health information is a common good of society, this study sought to map initiatives that addressed disciplines on health information in undergraduate education in order to outline an approach to the development of disciplines on this theme. Therefore, an exploratory research was developed to investigate undergraduate courses on health information offered by higher education institutions. To this end, three higher education institutions were selected that contemplate this perspective, namely: University of São Paulo (Brazil), University of Victoria (Canada) and Instituto Politécnico de Leiria (Portugal). From the exploratory study, it is concluded that it is possible to approach subjects on health information in undergraduate courses, following different perspectives. This study proposes that disciplines on health information be considered that cover, at least, themes on: a) uses of health information; b) informational objects in health; c) communication in health; d) organization, representation and retrieval of information in the health field; e) information technologies associated with health information. Different institutional and social realities can interfere in the process of consolidating curricular innovations in undergraduate education. Therefore, an in-depth reflection is necessary before any change or curricular proposal.